Knowledge of Posyandu Cadres in Stimulating Early Childhood with Special Needs - Kehok, Suprihatin; Linaty, Leiliana; maulidina, Citra Ashri; Putri, Aisyah Winna; Rosifah, R (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
Posyandu cadres are the spearhead of health education for the community, which means that they are the driving force, educators and servants of the community. In order to help achieve these goals, this community service study aims to determine and improve the knowledge of posyandu cadres in stimulating early childhood with special needs. This research was conducted in Kecamatan Wiradesa. The participants are posyandu cadre from Kecamatan Wiradesa who were appointed by the health service team and health center based on proportions with a total of 2 posyandu cadre for every village and sub-district in Wiradesa. There were 32 participants including students of Undip who are participating in KKN who did the pretest and 27 participantswho did the po t test. The data was analysed using simple statistic. Betwen the pre and post-test, the participants were given technical guidance on how to stimulate early childhood children with special needs in a simple way. It is found that the posyandu cadres’ knowledge were improving between before and after the lectures by 10%. The number of participants was very small so that the results of this activity cannot be used as a standard in assessing theknowledge of posyandu cadres in general. This activity has increased the knowledge of posyandu cadres who participated in this activity in stimulating early childhood with special needs.